Retrospective study on the incidence of envenomation and accessibility to antivenom in Burkina Faso. Issue 1 (December 2016) - Gampini, Sandrine; Nassouri, Sonia; Chippaux, Jean-Philippe; Semde, Rasmané
Abstract Background Snakebite is a common neglected public health issue, especially in poor rural areas of sub-Saharan Africa, Asia and Latin America. Passive immunotherapy with safe and effective antivenom is the only approved treatment for it. This study aimed to determine the incidence of snakebites, and to assess the availability and accessibility of antivenoms, from 2010 to 2014, in Burkina Faso. Methods The assessment of snakebite cases managed in all health facilities from 2010 to 2014 was performed from the Statistical Yearbook of the Ministry of Health. Antivenom consumption data were collected from the drug wholesalers established in Burkina Faso. Results Snakebites are among the five leading causes of consultations in health districts. From 2010 to 2014, 114, 126 envenomation cases occurred in Burkina Faso, out of which 62, 293 (54.6 %) victims have been hospitalized resulting in 1, 362 (2 %) deaths. The annual incidence and mortality were respectively 130 bites and 1.75 deaths per 100, 000 inhabitants. The amount of antivenom sold by wholesalers were 5, 738 vials with a total cost of US$ 539, 055 (annual average = US$ 107, 811). The high cost of these antivenoms (between US$ 42 and 170 per dose according to brand) limited their use by rural people, the main victims of snakebites, whose income is insufficient. Thus, only 4 % of patients received antivenom treatment over the past five years. The price of antivenom was reduced in 2015 to US$ 3.4 by a public drug wholesaler. Conclusion The study confirmed the high burden of snakebites in Burkina Faso. To better manage envenomation, Burkina Faso implemented a strategy consisting in seeking affordable sources of antivenom supply of good quality and innovative mechanisms of subsidy.